Writing the Arab-Israeli Conflict: Pragmatism and Historical Inquiry - Isacoff, Jonathan B. (Lexington Books, 2006)
Nearly all empirical work in political science is fundamentally historical, yet very little attention has been given to the problem of grounding claims to historical knowledge. In Writing the Arab-Israeli Conflict Jonathan B. Isacoff constructs the nature of historical knowledge by deftly examining the multiple histories of the Arab-Israeli conflict written by generations of Israeli scholars. He also undertakes briefer analysis of literature, drawn from both historians and political scientists of the Vietnam War, demonstrating that historical revisionism is not unique to the study of the Middle East. Focusing on different schools of historical interpretation Writing the Arab-Israeli Conflict argues for a pragmatist approach in the tradition of John Dewey. Most importantly, this exceptional work suggests a number of practical methodological measures that can be taken to produce more sophisticated and nuanced political science scholarship.